The later Stuart Church, 1660-1714 - Tapsell, Grant (Politics, culture, and society in early modern Britain., 2018)
The later Stuart Church, 1660-1714 features nine essays written by leading scholars in the field and offers new insights into the place of the Church of England within the volatile Restoration era, complementing recent research into political and intellectual culture under the later Stuarts. Sections on ideas and people include essays covering the royal supremacy, the theology of the later Stuart Church and clerical and lay interests. Attention is also given to how the Church of England interacted with Protestant churches in Scotland, Ireland, continental Europe and colonial North America. A concluding section examines the difficult relationships and creative tensions between the established Church in England, Protestant dissenters, and Roman Catholics. The later Stuart Church is intended to be both accessible for students and thought-provoking for scholars within the broad early modern field.